Sediment dynamics and stratigraphic architecture of a mixed carbonate-siliciclastic ramp: The Upper Ordovician (Hirnantian) Ellis Bay Formation, Anticosti Island, Quebec, Canada - Farley, Claude (University of Ottawa (Canada), 2008)
The Upper Ordovician (Hirnantian) Ellis Bay Formation on Anticosti Island, Quebec, Canada provides a unique opportunity to study the stratigraphic architecture of mixed carbonate-siliciclastic deposits that formed during a period of major glaciation on a storm-influenced, slowly subsiding tropical ramp. The west-east-trending Ellis Bay outcrop belt is ∼180 km long, slightly oblique to the paleoshoreline, and offers superb coastal exposure at both ends of the island. The western sections (90 m thick) consist of stacked cycles of mid- to outer-ramp, storm-dominated carbonates with argillaceous mudstones. Inner-ramp oncolitic and reefal carbonates are also present in the uppermost part of the formation. The thinner eastern sections (45 m thick) are composed of basal sandstone and argillaceous mudstone units forming a continuous succession from (1) incised-valley fill to (2) storm-influenced delta to (3) storm-dominated strandplain deposits. Overlying these basal sandstones are mid- to outer-ramp, mixed carbonate-siliciclastic tempestites capped by pure carbonate tempestites and, finally, oncolitic and reefal units that correlate with those in the western section. The gradual upward decrease in siliciclastic content in the eastern sections is attributed to the incremental migration (avulsion) of a siliciclastic-supplying delta confined to the eastern Anticosti Platform. Alternatively, it could result from river avulsion coupled with a gradual shift from relatively humid to more arid climatic conditions. Despite these important lateral facies changes, the recognition of four major transgressive-regressive sequences allows a precise correlation between the western and eastern sections. These sequences (or cycles) are likely driven by glacio-eustasy in association with the end-Ordovician Gondwanan glaciation.
Keywords: Geology.